Flood Prevention and Maximised Wood Production at the Same Time: Sustainable Forestry in the Swiss Nineteenth Century - Martin Stuber (Global Environment)
Previous research saw the nationwide implementation of sustainable forestry in the Swiss nineteenth century primarily as a response to the threat of flood disasters. In contrast, this article shows that Swiss sustainability pioneers aimed just as much at increasing wood production. With the Maximum Sustainable Yield they tried to meet the growing energy needs of the emerging industrial society. The argument of using sustainable forestry to meet future wood shortages only gained political clout in combination with flood prevention, which linked the intergenerational perspective of future wood needs with the acute disaster threat of the present. In this way, it was possible to overcome antagonisms between the scientifically trained forestry pinoniers and the rural societies. Together with the skillful setting of economic framework conditions, this was decisive for the implementation of sustainability as a participatory process, which was characteristic of Switzerland.